General aspects of cadmium: transport, uptake and metabolism by the kidney. - Nordberg, M (1984)
Cadmium taken up from lung and gastrointestinal tract is transported via blood to liver and kidney. On long-term exposure to cadmium, renal tubular dysfunction develops in humans and experimental animals. Data from animal experiments demonstrate that initially after exposure cadmium in blood is bound to albumin and proteins with higher molecular weight. Such cadmium is mainly taken up in liver. For a few days after exposure cadmium exists as metallothionein in plasma and blood cells. After both single and long-term administration of cadmium bound to metallothionein, cadmium is taken up by the kidney. The concentration of metallothionein-bound cadmium in plasma is quite low due to continuous renal clearance. Cadmium from metallothionein is taken up in renal tubules by pinocytosis and subsequently degraded in lysosomes, thereby releasing cadmium which stimulates de novo synthesis of metallothionein but also binds to reabsorbed metallothionein. Catabolizing and rebinding are continuous and prevent excretion of cadmium. Because of differences in transport, renal metabolic handling forms of cadmium are also different for different forms of cadmium administered and rate of administration. A single dose of metallothionein-bound cadmium given intravenously is almost immediately and completely taken up in the renal tubule. Under such conditions, resynthesis and rebinding processes are insufficient to sequester cadmium from sensitive tissue receptors, and renal damage occurs at total tissue concentrations much lower than when renal cadmium concentrations rise slowly. This explains the wide range (10-200 micrograms Cd/g wet weight) of cadmium in the renal cortex that associated with renal tubular dysfunction in experimental animals.